Mission in the context of margins - Jin-Kwan, Kwon (ed.); Larbeer, P. Mohan (ed.) (Bangalore, BTESSC., 2015)
" ... 10th Dialogue Programme held in Visthar Academy of Justice and Peace based at Dodda Gubbi in Bangalore, India, met under the theme, "Mission in the Context of Margin" from 19-21 August, 2014"--Page 299
Keywords: Dalits.-- Missions.-- India.-- Congresses; Intouchables.-- Missions, India; Marginality.--Social Religious aspects.-- Christianity; Minjung theology.-- Congresses; People with social disabilities.-- Missions.-- Congresses; Theology, Doctrinal.-- Congresses